BRCA1 and BRCA2 mutations sensitize to chemotherapy in patient-derived pancreatic cancer xenografts - Lohse, I (Br J Cancer, 2015)
BACKGROUND: Germline mutations of the BRCA tumour suppressors have been associated with increased risk of pancreatic cancer. Clinical evidence suggests that these patients may be more sensitive to treatment with cisplatin. As the frequency of germline BRCA mutations is low, definitive experimental data to support the clinical observations are still missing. METHODS: We tested gemcitabine and cisplatin sensitivity of four BRCA1 and BRCA2 mutant and three BRCA1 and BRCA2 wild-type (WT) patient-derived pancreatic cancer xenografts. RESULTS: We observed treatment sensitivity to gemcitabine and cisplatin in the BRCA WT and mutant models. The BRCA1 and BRCA2 mutant xenografts were significantly more sensitive to cisplatin although these models also showed sensitivity to gemcitabine. The BRCA1 and BRCA2 WT models showed sensitivity to gemcitabine but not cisplatin. Treatment sensitivity in the xenograft models closely resembled treatment response in the corresponding patients. DISCUSSION: We have characterised a panel of xenografts derived from pancreatic cancer patients carrying germline BRCA mutations, and shown that their genetic features resemble the patient donor. Our results support further clinical testing of treatment regimens combining gemcitabine and platinum drugs in this patient population, as well as preclinical research aiming to identify mechanisms of cisplatin resistance in BRCA mutant pancreatic cancers.